2016
DOI: 10.1017/gmh.2015.28
|View full text |Cite
|
Sign up to set email alerts
|

Does poverty alleviation decrease depression symptoms in post-conflict settings? A cluster-randomized trial of microenterprise assistance in Northern Uganda

Abstract: Background.By 2009, two decades of war and widespread displacement left the majority of the population of Northern Uganda impoverished.Methods.This study used a cluster-randomized design to test the hypothesis that a poverty alleviation program would improve economic security and reduce symptoms of depression in a sample of mostly young women. Roughly 120 villages in Northern Uganda were invited to participate. Community committees were asked to identify the most vulnerable women (and some men) to participate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
28
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 16 publications
3
28
1
Order By: Relevance
“…This study shows that adding a discussion group focused on challenging inequitable gender norms to a savings group overall significantly reduced women's posttraumatic stress symptoms compared with a savings group alone. These findings add to mixed findings from other studies, including a recent economic intervention study in eastern DRC that yielded secondary mental health benefits (Glass et al 2017 ) as well as studies on two economic interventions in conflict-affected DRC and northern Uganda that did not improve mental health (Bass et al 2016 ; Green et al 2016 ).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This study shows that adding a discussion group focused on challenging inequitable gender norms to a savings group overall significantly reduced women's posttraumatic stress symptoms compared with a savings group alone. These findings add to mixed findings from other studies, including a recent economic intervention study in eastern DRC that yielded secondary mental health benefits (Glass et al 2017 ) as well as studies on two economic interventions in conflict-affected DRC and northern Uganda that did not improve mental health (Bass et al 2016 ; Green et al 2016 ).…”
Section: Discussionsupporting
confidence: 56%
“…Two recent studies have examined the impact of women's economic empowerment on IPV and mental health in conflict-affected settings and yielded mixed findings regarding mental health. A cash grant with business skills training for women in northern Uganda did not reduce IPV or symptoms of depression in the treatment group (Green et al 2016 ). However, a recently completed trial of a livestock asset transfer intervention in eastern DRC showed significant reductions in symptoms of anxiety and PTSD, although it did not significantly reduce IPV more than the control group (Glass et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence from experimental interventions may be able to contribute key data towards estimating the relative contribution of each link in the SES-mental health cycle: There are a growing number of (a) poverty reduction programs that assess mental health outcomes and (b) mental health interventions that assess economic outcomes ( Lund et al, 2011 ). For example, Mexico’s Opportunidades conditional cash transfer program has shown improved mental health outcomes, although not all programs have been successful ( Ozer et al, 2011 , Madhani et al, 2015 , Green et al, 2016 , Kilburn et al, 2016 ). Evaluations of the economic impact of mental health interventions (addressing the social drift hypothesis) are still relatively rare.…”
Section: Discussionmentioning
confidence: 99%
“…It is a standardized index of days ill, a subjective "overall" health question, and three activities of daily living (walking a distance, carrying a heavy load, and working on a farm). See Appendix D for component treatment effects.27 Also, as shown byGreen et al (2015b), there is also no change in mental health, as measured by an index of 35 symptoms of depression and distress.28 Means and treatment effects for individual components are available in Appendix D.…”
mentioning
confidence: 99%